Interventional Algorithm in Gastrointestinal Bleeding—An Expert Consensus Multimodal Approach Based on a Multidisciplinary Team. (24th June 2020) - Rodrigues, Anabela; Carrilho, Alexandre; Almeida, Nuno; Baldaia, Cilénia; Alves, Ângela; Gomes, Manuela; Gonçalves, Luciana; Nunes, António Robalo; Pereira, Carla Leal; Silva, Mário Jorge; Aguiar, José; Orfão, Rosário; et al.
The approach to the patient with gastrointestinal bleeding (GIB) can be very complex. A multidisciplinary panel of physicians with expertise in Gastroenterology, Anesthesiology, and Transfusion Medicine worked together to provide the best knowledge and guide clinical practitioners in the real setting of health institutions, characterized by disparate availability of human and technical resources. The authors propose a global and personalized approach according to different clinical scenarios to improve the outcomes of patients with GIB, for whom the reduction of inappropriate transfusions is crucial. The goal of this document is to provide clear and objective guidance through interventional algorithms toward a goal-directed approach according to the clinical situation and supported by the latest available scientific data on GIB management in different settings.